Pengembangan Daerah Pesisir sebagai Objek Pariwisata di Kecamatan Bunobogu Kabupaten Buol - Rosma Kadir (Universitas Negeri Gorontalo, 2023)
Botugolu Village, Bunobogu District, Buol Regency, Central Sulawesi Province, is one of the villages that has tourism potential that can have a positive impact on the development and progress of Buol Regency if a development strategy is carried out for this village. The development of tourist villages that have tourism potential is part of the vision and mission of the village head. This is very important to encourage the improvement of the community's economy. However, the obstacles in developing the tourism resources are the access road to the tourist attraction and the inadequate environmental conditions. This obstacle can be overcome through community participation that utilizes local potential to be able to jointly improve road access and care for the environment for the development of tourist villages. The principle of community participation is the main element in developing a tourist village launched by the local government. Thus, the Village Development KKNT program is very appropriate to be implemented to support local government programs through tourism development in improving the community's economy. The community service program to build the KKNT village, which will be implemented in Botugulo Village for two months, is expected to provide benefits for formulating village government activity program policies for the development of tourism villages based on the Village SDGs. In addition, it can improve the community's economy so that it requires community participation in the development of tourist villages. The output of this KKNT is increasing community knowledge and being able to innovate based on the results of lecturer service to improve people's living standards according to the achievement of SDGs, the existence of village policy formulations that include achieving SDGs targets related to Village Care for the Environment and Community Economic Improvement and the existence of community groups that are responsive to the potential of tourism villages and the economy of the community as well as environmental care groups.